Opportunity and connectivity : selecting land managers for involvement in a conservation corridor linking two protected areas in the Langkloof Valley, South Africa - McClure, Alice (Rhodes University, Faculty of Science, Department of Environmental Science, 2011)
The Eden To Addo Corridor Initiative aims to connect formally protected areas in a conservation corridor from the coastal area of the Eden District near Plettenberg Bay, Western Cape, South Africa to the Addo National Elephant Park, Eastern Cape, South Africa. The corridor will incorporate government and privately owned land, and will be an attempt to maintain ecological processes at a range of spatial and temporal scales. The Langkloof Valley lies between the Baviaanskloof World Heritage Area and the Tstitsikamma National Park; two formally protected areas that will be incorporated into the Eden To Addo Corridor. Spatial prioritization analyses allow conservation planners to select areas that should be targeted for conservation action based on a range of criteria. Historically, ecological criteria have been included mostly alone in spatial prioritization. Recently, the idea of 'conservation opportunity' has emerged in the field of conservation planning; the notion suggests that a range of different types of data should be included in processes to spatially prioritise for conservation. By including those data defined as 'human' and 'social' data into prioritising activities, the feasibility of conservation plans can be accounted for, but historically conservation planners have failed to do so. I conducted a literature review that demonstrated that although the importance of human and social data are acknowledged in the conservation planning literature, these data that define opportunity are rarely actually included in spatial prioritisation analyses. I then carried out a social assessment that allowed me to define the social and human context of our study area and, specifically, what stewardship instruments land managers in the Langkloof would be prepared to engage. We found that land managers were generally willing to engage, but lacked the financial capacity to adopt conservation methods. Using a subset of the social and human data that were collected in the social assessment, I trialled a new Decision Support Software to fuse those data with ecological data in a novel attempt to identify priority areas for conservation action based on ecological integrity and feasibility. We also scheduled (ranked) land managers to approach for conservation action with a focus on local champions and clusters of land managers displaying strong conservation characteristics. Two corridors were identified; a major corridor in the western region of the valley and a secondary corridor closer to the middle. The members of the Initiative have been briefed on the outcomes, which provided them an opportunity to provide feedback; it is hoped that the framework of this study can be used for planning future connections. The Eden To Addo Corridor Initiative sent out a stewardship extension officer in February 2011 to approach those land managers areas that were identified. This planning exercise is a good demonstration of how, by collaborating effectively, academic conservation planners can contribute to supporting decision making by organizations that are implementing conservation action.
Keywords: Corridors (Ecology) -- South Africa -- Eastern Cape; National parks and reserves -- South Africa; Landscape ecology -- South Africa; Wildlife conservation -- South Africa; Conservation of natural resources -- South Africa; Land use -- South Africa -- Planning